2015
DOI: 10.1103/physrevlett.114.103004
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Molecular Orbital Structure in Lateral Electron Momentum Distributions from Strong-Field Ionization

Abstract: Strong-field ionization of aligned diatomic and polyatomic molecules such as O 2 , N 2 , C 2 H 4 , and others in circularly polarized laser fields is investigated theoretically. By calculating the emission-angle-resolved lateral width of the momentum distribution perpendicular to the polarization plane, we show that nodal planes in molecular orbitals are directly imprinted on the angular dependence of the width. We demonstrate that orbital symmetries can be distinguished with the information obtained by observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 57 publications
1
22
0
4
Order By: Relevance
“…For instance, this HHG process offers an ideal framework for the study of strong-field dynamics [37]. Moreover, as the CPLP has already shown its great power in the application of (one-shot) imaging or structure detection of molecules [39][40][41][42], the HHG by CPLP can be potentially utilized for the imaging and detection of molecules with an all-optical method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this HHG process offers an ideal framework for the study of strong-field dynamics [37]. Moreover, as the CPLP has already shown its great power in the application of (one-shot) imaging or structure detection of molecules [39][40][41][42], the HHG by CPLP can be potentially utilized for the imaging and detection of molecules with an all-optical method.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the higher efficiency is mainly contributed in the recombination step and is at least partly due to the higher recollision probability for molecules. Since this HHG process involves the unique recollision mechanism under a circularly polarized laser field, it will stimulate new potential applications, such as offering an ideal framework for study of strong-field dynamics [37] and (one-shot) imaging or structure detection of molecules with all optical methods [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these activities can still be traced back to origins in the work done in the group of Peter Knight during the years 2001/2002. For example, the imaging of molecular structure still plays a major role in current work, see [120].…”
Section: B Atoms and Molecules In Strong Laser Fieldsmentioning
confidence: 99%
“…In these studies, the dipole approximation are widely accepted when a Ti:Sapphire laser pulse with an intensity below 10 16 W/cm 2 is introduced [4]. Within the dipole approximation, the photoelectron momentum distribution along the laser propagation direction has a symmetric distribution centered at zero (see Ref [5][6][7] for example).…”
Section: Introductionmentioning
confidence: 99%